Electron Microscopy and Optical Characterization of Cadmium Sulphide Nanocrystals Deposited on the Patterned Surface of Diatom Biosilica. (7th May 2009) - Gutu, Timothy; Gale, Debra K.; Jeffryes, Clayton; Wang, Wei; Chang, Chih-hung; Rorrer, Gregory L.; Jiao, Jun
Abstract : Intricately patterned biosilica obtained from the shell of unicellular algae called diatoms serve as novel templates for fabrication of optoelectronic nanostructures. In this study, the surface of diatom frustules that possessed hierarchical architecture ordered at the micro and nanoscale was coated with a nanostructured polycrystalline cadmium sulphide (CdS) thin film using a chemical bath deposition technique. The CdS thin film was composed of spherical nanoparticles with a diameter of about 75 nm. The CdS nanoparticle thin film imparted new photoluminescent properties to the intricately patterned diatom nanostructure. The imparted photoluminescent properties were dependent on the CdS coverage onto the frustules surface. The intrinsic photoluminescent properties of the frustules were strongly quenched by the deposited CdS. The origin of PL spectra was discussed on the basis of the band theory and native defects.